Propositions and the Meaning of ‘Ought’ - Fusco, Melissa (Journal of moral philosophy, 2018)
Matthew Chrisman’s new book, The Meaning of ‘Ought’: Beyond Descriptivism and Expressivism in Metaethics, presents a semantic treatment of the deontic modal operator Ought designed to address the problem of subject-sensitivity: why, for example, “I ought to dance with you” might be true, while “You ought to dance with me” is false. Such sentence-pairs challenge the view that Ought is an operator on propositions—an assumption which is common ground amongst both classical and much contemporary work. Chrisman argues that rather than propositions, the operator Ought takes as its argument a non-propositional formal object called a practition. In this review, I discuss the inspiration and formal features of this treatment. While I argue that the distinction between practitions and propositions is not adequately characterized in Chrisman’s compositional semantics, subject-sensitivity raises interesting questions about the metaethical assumptions at play in the formal semantics—including the worry that treating Ought as a propositional operator illicitly begs the question in favor of broadly consequentialist views.